Comparison of volatility and performance of shares in Indonesia, Malaysia, China and America (Study on the content, FBMS, DJICHKU and DJIMI) - Wulandari, Resti (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Starting from the trade war between the United States and China in 2018-2019 shows the challenges of a global economic slowdown which is characteristic of the domestic economy, namely the performance of the capital market and the volatility of stock prices, causing the capital development market to experience a decline from 2015-2019 which has an impact on the Indonesian capital market. Malaysia, China and America. The purpose of this study is to analyze the results of the volatility difference test and the performance of Islamic stocks in Indonesia (ISSI), Malaysia (FBMS), China (DJICHKU) and America (DJIMI) and to see whether Indonesia's volatility is lower than the three countries and the performance of the Indonesian stock exchange. better than the other three countries. This type of research is comparative descriptive. The sampling technique used saturated sampling, namely all Islamic stocks that are members of the four countries. This study uses the ARCH/GARCH model to estimate volatility and calculate performance using the Sharpe, Treynor and Jensen methods using re-measurement different test tools. The results show that the volatility of Indonesian stock prices (ISSI) is not lower when compared to the three countries because Indonesia's volatility is at the second level and for the performance of Indonesian Islamic stocks (ISSI) has a better performance when measured by Jensen. method, if using the American treynor method. have a better performance than Indonesia, Malaysia and China.